Optimization of transferent conducting oxides in heterojunction solar cells by excimer laser annealing - Suárez Berrú, Jerzy Javier (2015)
One of the most important problems in our society is the lack of clean energy sources to overcome the energetic crisis and global warming. For this reason, I enrolled “Master en Energías Renovables y Eficiencia Energética” at UNI. This master gave me a good training and knowledge to face real problems concerning renewable energies. I chose photovoltaic solar energy because my major interest in physics are solid state physics and material science, in this manner I could bring together my two passions for material science and green energy. In April 2014, I had the unique chance to go to Institut National de l’Energie Solaire (INES) to make an internship for five month. The principal objective of this internship at Laboratoire de Heterojunction (LHET) in INES was to test the Excimer Laser Annealing (ELA) to improve HET solar cell performance through the amelioration of optical transmission and through the reduction of electrical resistance of Indium Tin Oxide (ITO). We also studied the impact of ELA on the most important Transparent Conducting oxides (TCO) in research at INES, such as: ITO (Indium Tin Oxide), AZO (Aluminum doped Zinc Oxide) and IOH (hydrogen doped Indium Oxide). We measured different physical properties of thin films such as: optical transmission, electrical conductivity, sheet resistance, index of refraction. We measured also the size of ITO grains by SEM. We also studied electrical properties of two different solar cells (R&D and Pilot line measuring I-V curve, lifetime of charge carriers, Pseud Fill Factor, series and shunt resistance in solar cell. Almost all these techniques are covered briefly in this thesis to show the fundamentals of physics of the electronic devices to know what we were really measuring. At the end of this report, conclusions are presented in two parts one for the characterization of TCO thin films and the other one for the HET solar cell characterization.